Menggali Dan Mengembangkan Potensi Daerah Dalam Perwujudan Otonomi Daerah: Perspektif Konseptual - Nuryasman MN (Jurnal Ekonomi, 2008)
The implementation of the territory autonomy has been for more than 8 years, but until today, it cannot give any added value to the territories yet. In fact, most territories do not know what they should do in managing their territory such as how to do administration and how to develop sources of economic potential. Until now, most territories still use funds from Central Government to finance their activities. Although there is a regulation stating that local governments must use funds from their local potentials and the funds from the Central Government are just support. The objective of this paper is to help local governments discover the local economic potential. For that purpose, there are some methods or theories that can be used: (1) comparative advantage theory; (2) economic-based theory; (3) shift-share analysis; (4) input-output analysis. The use of every method is determined by the availability of data sources and local government capacity to develop their territory.